Amino Acids: Nontoxic and Cheap Alternatives for Amines for the Synthesis of Benzoxazoles through the Oxidative Functionalization of Catechols. Issue 5 (16th January 2020) - Sharghi, Hashem; Aboonajmi, Jasem; Aberi, Mahdi; Shekouhy, Mohsen
Abstract: The nano magnetic Fe3 O4 (NM−Fe3 O4 ) was applied for the synthesis of benzoxazoles via a C(aryl)−OH functionalization of catechol derivatives and amines in ethanol at room temperature. In the next step, amino acids have been applied as nontoxic and cheap alternatives for amines. The obtained products were similar with the regular amines case. This is the first report about the application of amino acids as alternatives for primary amines in organic synthesis. Furthermore, the presented method was successfully applied toward the synthesis of desired products in large scales. Abstract :